2022
DOI: 10.1093/jambio/lxac003
|View full text |Cite
|
Sign up to set email alerts
|

Association between antimicrobial consumption and resistance rate ofEscherichia coliin hospital settings

Abstract: Aims This study aims to quantify antimicrobial consumption (AMC) and antimicrobial resistance (AMR) in tertiary care hospitals in Pakistan. Methods and results This observational study was conducted at two tertiary care hospitals of Pakistan over a 1-year period. The AMC and resistance patterns of Escherichia coli isolates collected from hospitals were observed and analysed using the pearson correlation coefficient. AMC in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The emergence of MDR E. coli isolates is causing therapeutic failures that are a serious public health threat and lead to high morbidities and mortalities in hospital settings ( 43 ). This study reported a high resistance rate for fluoroquinolones (95–100%), cephalosporins (88–95%), penicillins (82–97%), and aminoglycosides (58%).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of MDR E. coli isolates is causing therapeutic failures that are a serious public health threat and lead to high morbidities and mortalities in hospital settings ( 43 ). This study reported a high resistance rate for fluoroquinolones (95–100%), cephalosporins (88–95%), penicillins (82–97%), and aminoglycosides (58%).…”
Section: Discussionmentioning
confidence: 99%
“…Extreme use of antibiotics for livestock management practices and conducive horizontal gene transfer systems within the E. coli family could be linked to the recorded high resistance. This poses a greater threat of zoonotic disease outbreaks in these countries [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These high rates need to be urgently addressed, given the already rising rates of AMR in Pakistan, and ongoing challenges to reduce this as part of their national action plan to reduce AMR [ 78 , 79 ]. We are seeing antimicrobial stewardship programs (ASPs) being successfully introduced among hospitals across LMICs to improve appropriate antibiotic prescribing despite initial concerns, and these can serve as exemplars for Pakistan in the future [ 44 , 45 , 80 , 81 , 82 , 83 ]. We will be following this up in future studies now that the AWaRe book has been published, providing guidance for a range of infections, combined with suggested prescribing and quality indicators [ 60 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive prescribing of antibiotics is a concern, as their inappropriate and unjustified use increases antimicrobial resistance (AMR) [ 40 , 41 , 42 , 43 , 44 , 45 ]. Increasing AMR appreciably increases morbidity, mortality and costs, and has been described as the next pandemic unless addressed [ 42 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%